Improved safety profile of inactivated Neethling strain of the Lumpy Skin Disease Vaccine - Matome Selina Matsiela; Leeann Naicker; Vusi Saul Dibakwane; Nomfundo Ntombela; Thandeka Khoza; Nobalanda Mokoena (Vaccine: X, 2022)
The Lumpy Skin Disease Virus (LSDV) Neethling vaccine strains have been used for decades for prophylactic immunization of domestic ruminants against the disease. Commercial products against Lumpy skin disease are supplied as live attenuated vaccines and often are associated with adverse reactions warranting studies towards development of safe and efficacious vaccine alternatives. The present study was designed to investigate the ability of Montanide™ Gel 01 PR adjuvanted inactivated Neethling vaccine strain of the lumpy skin disease to induce immune response in rabbits. Complete virus inactivation was achieved following treatment of live vaccine strain with binary ethyleneimine (BEI) at 2 mM final concentration. Inactivated virus antigen, formulated with Montanide™ Gel 01 was injected at 1,00E + 05 and 1,00E + 06 TCID50 per dose in rabbits. The second injection with same vaccine dosages was administered 21 days after the primary vaccination. Rabbits that received a 1,00E + 05 TCID50/dose of inactivated LSDV vaccine formulation induced maximum neutralizing antibody titres on day 13 post second vaccinations. Rabbits vaccinated and prime boosted with the 1,00E + 06 TCID50/dose of inactivated LSDV vaccine formulation, induced neutralizing antibody titres on day 14 after first vaccination. The maximum antibody titres for the 1,00E + 06 TCID50/dose of the inactivated LSDV vaccine formulation was obtained on day 35 post vaccination. The 1,00E + 06 TCID50 dose of the inactivated LSDV vaccine Montanide™ Gel-01 PR formulation induced higher neutralizing antibodies. The MontanideTM Gel-01 PR offers safer profile to oil adjuvants and can be developed further to protect target animals against LSDV in non-endemic areas.